Effects of a 4-Week Plyometric Training on the Jumping Performance of Basketball Players / Wee Eng Hoe,Floreta Mudah and Tan Chee Hian - Wee, Eng Hoe; Mudah, Floreta; Tan, Chee Hian (Faculty of Sports Science and Recreation, 2011)
This study examined the effect of 4-week plyometric training programme on the jumping performance of undergraduate male basketball players. A total of 20 basketball players from the inter-faculty game at a public university were selected to participate in this study. The subjects were aged 20-23 years (mean = 21.3 + 1.12). Convenience sampling was used to select the students and subsequently randomly assigned to the control (n=10) and experimental (n=10) groups. Both groups were trained according to the compulsory training programme three times a week for four weeks. Additional plyometric training was provided to the experimental group, twice a week on non training days. The Vertec equipment (VER Vertec Jump Trainer) was used to measure the vertical jumping ability of the subjects. Control and experimental groups showed significant improvement in the mean vertical jump scores during the post-test as compared with the pre-test (t= -2.45; p < 0.05; and t=-21.00; p<0.05 respectively). Experimental group exhibited greater improvement (11.17%) as compared to the control group (2.12%). In short, plyometric training improved the jumping performance of basketball players and it is recommended to be used as a training strategy in improving jumping performance not only in basketball but in other sport as well.